(3VeGfGJ Mbhb GdeQCI GdELQGFjI aj bhGfjf GdCMhGd GdTNUjI GdeUQjI (B:s (3GdMb aj GdJbGVj(B-(3GdMb aj GdJfajP (B/s - (3jhSa, SMQ YHO GdSJGQ EeGe,s 1971- ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI,s, 2012)
(3YfOeG JcJH HGMKI bGfhfjI Yf VeGfGJ Mbhb ELQGFjI ddeQCI GdeUQjI, aEfgG dG HO hCf JbOe HMKG LOjQG ddGgJeGe, aEPG cGfJ GdHGMKI CSJGPI LGeYjI adG HO Cf jJUa GdHMK HGdLOI hGdLOjI(B. (3hbO MQUJ GdOcJhQI (B: (3SMQ YHO GdSJGQ(B- (3aj TQMgG dJdc GdMbhb(B- (3Ydi GdOaGY Yf eHOC jNGda GdeHOC GdYGe(B. (3aGdCUd gh eSGhGI GdLejY aj GdMbhb hGdhGLHGJ, hcGfJ GdMQcI GdfSGFjI JfGOj OGFeG HGdeSGhGI GdbGfhfjI Hjf GdeQC hGdQLd(B. (3hdcf GdHGMKI hLOJ Cf gPg GdeSGhGI dG JMaX Mbhb GdeQCI, afGOJ HeHOC YOe GdeSGhGI GdbGfhfjI HjfgeG, hQCJ Cfg gh hMOg GdPj jMbb GdeSGhGI GdaYdjI Hjf GdeQCI hGdQLd(B. (3haj SHjd GdOaGY Yf eHOC YOe GdeSGhGI GdbGfhfjI, YQVJ GdHGMKI ddfUhU GdJTQjYjI aj GdbGfhf GdeUQj GdeJYdbI HGdJbGVj hHGdJfajP GdLHQj ddCMcGe hGdJj JfWhj Ydi GSJKfGAGJ ef GdbhGYO GdELQGFjI GdYGeI(B. (3hbO YfjJ GdHGMKI HTQM Jdc GdbhGYO GdNGUI TQMG eHSWG heJYebG eSJYjfI HGdabg hCMcGe GdbVGA(B. (3aChVMJ GdbGYOI GdNGUI HGdGNJUGU aj OYGhi GdfabI, hGdGNJUGU HTCf GdefY ef GdSaQ, hGdhdGjI GdJYdjejI, hYQVJ deG jJYdb HGdEYaGA ef GdQShe GdbVGFjI HGdfSHI dOYGhi GdfabI, hdELQGAGJ OYhi GdNdY hTQhW GdMce Hg, hJfGhdJ GdfaGP GdeYLd dCMcGe GdfabI, hGdbhGYO GdNGUI HJfajPgG LHQG(B. (3hdgPG aEf gPG GdHMK Sha jchf eQLYG eajOG ddbGVj hGdeMGej, hYhfG ddeQCI aj GdeWGdHI HMbhbgG(B. (3hSjMJd GdecGfI GdJj jSJMbgG aj GdecJHI GdbGfhfjI GdYQHjI(B. s
(3HHdjhLQGajI (B: (3UaMI (B149-161.s
Keywords: (3Mbhb GdeQCIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdfSGAs -- (3hVY bGfhfj, bhGfjf, EdN(B.s -- (3eUQs; (3GdCMhGd GdTNUjI (B((3abg ESdGej(B)s; (3GdCMhGd GdTNUjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3JfajP GdCMcGes -- (3eUQs; (3GdbVGAs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3bGfhf GdELQGAGJ GdeOfjI hGdJLGQjIs -- (3eUQs; (3bGfhf GdCMhGd GdTNUjI s